2003
DOI: 10.1016/s0195-6663(03)00037-0
|View full text |Cite
|
Sign up to set email alerts
|

Disgust sensitivity and meat consumption: a test of an emotivist account of moral vegetarianism

Abstract: Emotivist perspectives on moral reasoning hold that emotional reactions precede propositional reasoning. Published findings indicate that, compared with health vegetarians, those who avoid meat on moral grounds are more disgusted by meat [Psychol. Sci. 8 (1997) 67]. If, as per emotivist perspectives, such disgust precedes moral rationales for meat avoidance, then the personality trait of disgust sensitivity should generally be inversely related to meat eating. We surveyed 945 adults regarding meat consumption,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
87
1
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(102 citation statements)
references
References 54 publications
9
87
1
5
Order By: Relevance
“…Rothgerber (2014a) surveyed ''semi-vegetarians'' and vegetarians and found that ''semi-vegetarians'' see humans as being less similar to animals and express a lower level of expressed ''disgust'' towards meat than vegetarians do. By surveying 945 adults, Fessler et al (2003) found that ''moral vegetarianism conforms to traditional explanations of moral reasoning'' (p. 31).…”
Section: Knowledge and Skillsmentioning
confidence: 99%
“…Rothgerber (2014a) surveyed ''semi-vegetarians'' and vegetarians and found that ''semi-vegetarians'' see humans as being less similar to animals and express a lower level of expressed ''disgust'' towards meat than vegetarians do. By surveying 945 adults, Fessler et al (2003) found that ''moral vegetarianism conforms to traditional explanations of moral reasoning'' (p. 31).…”
Section: Knowledge and Skillsmentioning
confidence: 99%
“…Personal health and animal cruelty figure high on this list (Hoek et al 2004, 266, Lea andWorsley 2001, 127), while disgust or repugnance with eating flesh (Kenyon and Barker 1998, Rozin et al 1997, Santos and Booth 1996, association with patriarchy (Adams 1990), food beliefs and peer or family influences (Lea and Worsley 2001, 128) are also noted. Health vegetarians choose to avoid meat in order to derive certain health benefits or lose weight (Key et al 2006, Kim and Houser 1999, Wilson et al 2004, while ethical vegetarians consider meat avoidance as a moral imperative not to harm animals for food or other reasons (Fessler et al 2003, 31, Whorton 1994.…”
Section: Studies Of Vegetarians Have Identified a Variety Of Non-relimentioning
confidence: 99%
“…Exemplos como o vegetarianismo moral demonstram como alterações nos julgamentos morais podem ser provocadas por processos de deliberação e de reflexão (Sterelny 2012, p.141). O nojo e a repulsa que vegetarianos sentem por carne é uma consequência, não uma causa, de suas convicções morais (Fessler et al 2003). De forma semelhante, pessoas que consideram a homossexualidade repugnante podem tornar-se tolerantes em razão de processos de reflexão e, ao longo do tempo, modificar as suas intuições e sentimentos iniciais.…”
Section: Trolley Problems E Princípio Do Duplo Efeitounclassified